2016
DOI: 10.1017/jfm.2016.666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Stokes number on particle velocity and concentration distributions in a well-characterised, turbulent, co-flowing two-phase jet

Abstract: Simultaneous measurements of particle velocity and concentration (number density) in a series of mono-disperse, two-phase turbulent jets issuing from a long, round pipe into a low velocity co-flow were performed using planar nephelometry and digital particle image velocimetry. The exit Stokes number,$Sk_{D}$, was systematically varied over two orders of magnitude between 0.3 and 22.4, while the Reynolds number was maintained in the turbulent regime ($10\,000\leqslant Re_{D}\leqslant 40\,000$). The mass loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 67 publications
13
58
0
1
Order By: Relevance
“…According to far-jet asymptotics, this dynamical "skeleton" is expected to be universal also for swirling and nonaxisymmetric jets [44]. Future work should demonstrate the particular role of the observed structures and their contribution to mixing [21], aeroacoustics [45], and to the strong anisotropy and peculiarities of the concentration distribution in particle-laden jets [46]. The obtained basis can also be a good candidate for a Craya-type decomposition for inhomogeneous flows to inspect the role of helicity in the energy transfer [47][48][49].…”
Section: U(rxmt)mentioning
confidence: 81%
“…According to far-jet asymptotics, this dynamical "skeleton" is expected to be universal also for swirling and nonaxisymmetric jets [44]. Future work should demonstrate the particular role of the observed structures and their contribution to mixing [21], aeroacoustics [45], and to the strong anisotropy and peculiarities of the concentration distribution in particle-laden jets [46]. The obtained basis can also be a good candidate for a Craya-type decomposition for inhomogeneous flows to inspect the role of helicity in the energy transfer [47][48][49].…”
Section: U(rxmt)mentioning
confidence: 81%
“…Particles were located on a ring next to the centerline of the stream. Lau and Nathan [14] suggested a process of particle reorganisation (particle size < 40 μm) selected by Stokes number, resulting in significant particle migration to the jet axis or away from the centreline respectively for low values of Stokes number or for high values of Stokes number. For a given particle type and size in a fluid, the Stokes number increased with the mean velocity of the gas.…”
Section: Results: Particle Count In Zone 1 Andmentioning
confidence: 99%
“…Fluid dynamics investigations have been carried out to analyse the importance of Stokes numbers on the velocity and concentration distribution of a multiphase flow [14,15]. The authors showed that the flow outside of the nozzle is characterised by a process of particle reorganisation, resulting in significant particle migration towards the jet axis or away from the centreline respectively for low values of Stokes number and for high values of Stokes number.…”
Section: Introductionmentioning
confidence: 99%
“…For the configurations of θ j = 5 • [ Fig. 8(a)], it can be seen that the value of u /v exhibits two peaks, one in the shear layer (r/D c ≈ 0.15), consistent with an unconfined single jet, 38 and the other in the near wall region (r/D c ≈ 0.45). These locally high values imply a high degree of anisotropy in these regions, consistent with an important role of large-scale turbulence.…”
Section: B Turbulent Flow Fieldsmentioning
confidence: 99%